Relevansi Penyajian Laporan Keuangan Berdasarkan Pernyataan Standar Akuntansi Keuangan (PSAK) No. 109 Pada LAZIS NU - Arina Hidayati; Tri Joko Sulistiyanto; Kharisma Nawang Sigit; Muhammad Asrofi (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
Abstract Economic inequality can be minimized by increasing income distribution in public. One of equalization is regulated in Islam, namely through Zakat, Infaq and alms. This study aims to describe the relevance of the presentation of financial statements based on PSAK No. 109 at LAZIS NU, Limpung District, Batang Regency. The research method used is qualitative with a case study approach. The author uses interview data collection techniques, observation and document review. The analytical technique used in this research is Spradley domain analysis. This research is focused on LAZIS-NU, Limpung District. The results showed that LAZIS NU only presented cash flow financial statements. Meanwhile, reports on changes in funds, changes in assets under management and notes to financial statements have not been presented properly. This study can serve as a comparison with other studies to determine the level of conformity of the presentation of financial statements based on PSAK No. 109 on zakat infaq and alms financial institutions.